2020
DOI: 10.1088/1742-6596/1515/2/022048
|View full text |Cite
|
Sign up to set email alerts
|

On the role of hydrated calcium carboaluminate in the improvement of the production technology of alumina from nephelines

Abstract: The coagulation properties of HCCA in the system “aluminate solution - nepheline sludge” were studied, which allowed to improve the processes of thickening and washing of nepheline sludge. Solutions were developed aimed at the improvement of the coarse alumina production technology on the basis of increasing the efficiency of the carboaluminate method for separating Al (III) and Si(IV) hydroxo complexes and using the combined crystal growing modifier CaCO3 – HCCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Conventional ultrafine-grained materials with grain sizes in the scale of several micrometers are usually manufactured using thermomechanical processes. An ultrafine-grained structure cannot be obtained by classical methods because of dynamic reduction and recrystallization processes, as well as limitations in formability [ 20 , 21 , 22 , 23 , 24 , 25 ]. Ultra-thin and nanocrystalline materials have been the subject of extensive research for a long time because their mechanical properties allow us to expect great potential as structural materials.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional ultrafine-grained materials with grain sizes in the scale of several micrometers are usually manufactured using thermomechanical processes. An ultrafine-grained structure cannot be obtained by classical methods because of dynamic reduction and recrystallization processes, as well as limitations in formability [ 20 , 21 , 22 , 23 , 24 , 25 ]. Ultra-thin and nanocrystalline materials have been the subject of extensive research for a long time because their mechanical properties allow us to expect great potential as structural materials.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an achieving of the thermochemical activation by the addition of fluxing agents (i. e. Charcoal) to the kaolin-limestone mixtures in the sintering process would produce more low costeffectiveness and energy-efficiency by lowering the temperature limit of the phase transformation (i.e., dicalcium silicate C 2 S β to γ phases). Not only this, but also the charcoal addition extremely improving the physical surface properties of the self-disintegrated sinter powders and particles and hence enhancing the leaching process and maximizing the alumina percent recovery (Qiu et al, 2004;Sizyakov et al, 2013a;Sizyakov et al, 2013b;Sizyakov & Brichkin, 2018;Dubovikov et al, 2018;. In addition to the charcoal, previous researches indicated that the common other additive of inorganic fluxing agents were MgO, A1 2 O 3 , Fe 2 O 3 , BaO, B 2 O 3 , Na 2 O, K 2 O, P 2 O 5 , MnO 2 and Cr 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%
“…β-C 2 S to γ-phases). Moreover, the addition of charcoal would significantly improve the surface properties of the self-disintegrated sinter powders and particles and hence would increase leaching and maximize the alumina percentage recovery (APR; Qiu et al, 2004;Sizyakov et al, 2013aSizyakov et al, , 2013bDubovikov et al, 2018;Sizyakov & Brichkin, 2018;Li et al, 2019). Previous work showed that other compounds such as MgO, Al 2 O 3 , Fe 2 O 3 , BaO, B 2 O 3 , Na 2 O, K 2 O, P 2 O 5 , MnO 2 and Cr 2 O 3 , present either as chemical impurities or as fluxing additives to kaolin, were unfavourable because they stabilized the β-C 2 S phase and hence prevented self-disintegration (Wang et al, 2011;Yu et al, 2012Yu et al, , 2014Yu et al, , 2019Guo et al, 2014;Yan et al, 2017;Bazhirov et al, 2020).…”
mentioning
confidence: 99%
“…The formation, utilization and use of waste currently are one of the most pressing issues in the field of environmental safety and environmental protection both in Russia and worldwide [1,2,3]. This is due both to the rapid increase in the volume of production and consumption waste, and to the insufficiently high level of development of the waste management sector.…”
Section: Introductionmentioning
confidence: 99%